2023
DOI: 10.3390/informatics10010014
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to the Adoption of Digital Twin in the Construction Industry: A Literature Review

Abstract: Digital twin (DT) has gained significant recognition among researchers due to its potential across industries. With the prime goal of solving numerous challenges confronting the construction industry (CI), DT in recent years has witnessed several applications in the CI. Hence, researchers have been advocating for DT adoption to tackle the challenges of the CI. Notwithstanding, a distinguishable set of barriers that oppose the adoption of DT in the CI has not been determined. Therefore, this paper identifies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 91 publications
3
13
0
Order By: Relevance
“…This highlights the need for further education and awareness initiatives to disseminate knowledge about DTs and their potential applications in FM. These findings also agree with prominent gaps found by several studies [127,129,141]. The authors of [128] highlighted a lack of educational programs at universities that especially focus on addressing DTs.…”
Section: Main Challengessupporting
confidence: 88%
See 2 more Smart Citations
“…This highlights the need for further education and awareness initiatives to disseminate knowledge about DTs and their potential applications in FM. These findings also agree with prominent gaps found by several studies [127,129,141]. The authors of [128] highlighted a lack of educational programs at universities that especially focus on addressing DTs.…”
Section: Main Challengessupporting
confidence: 88%
“…The participants were also asked about their experience with DTs, BIM, the IoT, AI, and AR [43,126]. The survey also asked about the impact of missing information on their decision making and solicited suggestions for enhancing the DT framework [43,[127][128][129]. The survey included questions about participants' familiarity and understanding of DT technologies in FM [126,[129][130][131], the frequency of data collection for FSE maintenance [43,126], the expected benefits from DT technologies in FM [126][127][128][129], and the evaluation of DT technologies in FSE and fire evacuations [126,129,132].…”
Section: Survey Of Fm Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like any digitally encapsulated artefact or information technological method, digital twins are becoming increasingly well described from a technical point of view with intriguing managerial questions lagging behind (Holmstr€ om et al, 2019;Bhandal et al, 2022;Okrent and Vokurka, 2004). In this light, Opoku et al's (2023) recent review on adoption barriers of digital twins found that the literature is very concerned with legal, ethical, and technical factors on the organisation-if not even the industry-level. This view is shared by Saporiti et al (2023), and van der Horn and Mahadevan (2021), who call for more research on organisational culture as digital twin implementation challenge.…”
Section: Introductionmentioning
confidence: 99%
“…, 2022; Okrent and Vokurka, 2004). In this light, Opoku et al. ’s (2023) recent review on adoption barriers of digital twins found that the literature is very concerned with legal, ethical, and technical factors on the organisation-if not even the industry-level.…”
Section: Introductionmentioning
confidence: 99%